Writing the Revival: The Intersections of Methodism and Literature in the Long 18th Century. Issue 1 (January 2015) - McInelly, Brett C.
Abstract The Methodist revival attracted as much negative press as it did converts during the 18th century – in religious polemic, satiric verse, prose fiction, and dramatic script; the Methodists themselves likewise produced a rich body of spiritual autobiography and sacred verse, mostly in the form of the Methodist hymnal. This essay offers a survey of the scholarship that addresses the textual culture surrounding the revival, including critical assessments of the literature produced by the Methodists, its impact on the movement and Methodist religiosity, as well as discussions of the anti‐Methodist literature and how it registered within Methodism and the larger society. The essay also considers studies that connect Methodism and its literature to literary and cultural developments during the period, including developments in drama, the novel, and the Culture of Sensibility.